Inflation expectations and choices of households - Nathanael Vellekoop; Mirko Wiederholt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Do household in ation expectations affect consumption-savings decisions? We link survey data on quantitative in ation expectations to administrative data on income and wealth. We document that households with higher in ation expectations save less. Estimating panel data models with year and household fixed effects, we find that a one percentage point increase in a household's in ation expectation over time is associated with a 250-400 euro reduction in the household's change in net worth per year on average. We also document that households with higher in ation expectations are more likely to acquire a car and acquire higher-value cars. In addition, we provide a quantitative model of household-level in ation expectations.
Keywords: 330